Analysis of Technology Readiness of Generation Z Accountants with the Technology Acceptance Model in Adopting Artificial Intelligence Technology - Ni Putu Winda Ayuningtyas; Syarif Hidayah Lubis; Kharisma Austin Makaba (Eduvest - Journal of Universal Studies, 2024)
Everything related to Artificial Intelligence (AI) technology has a crucial role to play in helping to improve efficiency, lowering expenses, and optimizing decision-making across numerous industries, including accounting, where Generation Z accountants, particularly in Batam, must continuously develop their skills and readiness to leverage AI despite challenges related to data privacy and security. This research seeks to evaluate the readiness of a Generation Z accountant to embrace artificial intelligence (AI) technology by applying the Technology Acceptance Model (TAM). In the context of the fourth industrial revolution, AI adoption is crucial for improving efficiency and effectiveness in accounting practices. The study employs a quantitative approach with purposive sampling, involving 220 Generation Z accountant participants from Batam City. The analysis, conducted using the PLS-PM method in R programming and data processing with Google Colab statistics, reveals that the Technology Readiness (TR) variable significantly influences the interest of Generation Z accountants in adopting AI technology. While the perceived ease of use (PEOU) variable showed no significant effect, perceived usefulness (PU) emerged as the dominant factor in technology adoption. The R-Squared value of 0.920 indicates that 92% of the variables influencing AI technology adoption are explained by TR and PU. This study highlights the importance of technology readiness in helping Generation Z accountants adapt to technological advancements and offers recommendations for enhancing education, training, and technology development within the accounting profession.